The impact of the experimental curriculum "history of athletics in Ivano-Frankivsk region" on development of value-motivational character of the students of physical training and sports institutions - Kryzhanivska, Oksana; Fotuima, Oleksandr (Journal of Education, Health and Sport, 2015)
Kryzhanivska Oksana, Fotuima Oleksandr. The impact of the experimental curriculum "History of athletics in Ivano-Frankivsk region" on development of value-motivational character of the students of physical training and sports institutions. Journal of Education, Health and Sport. 2015;5(4):11-16. ISSN 2391-8306. DOI: 10.5281/zenodo.16537 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A11-16 https://pbn.nauka.gov.pl/works/552849 http://dx.doi.org/10.5281/zenodo.16537 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015. THE IMPACT OF THE EXPERIMENTAL CURRICULUM "HISTORY OF ATHLETICS IN IVANO-FRANKIVSK REGION" ON DEVELOPMENT OF VALUE-MOTIVATIONAL CHARACTER OF THE STUDENTS OF PHYSICAL TRAINING AND SPORTS INSTITUTIONS Oksana Kryzhanivska, Oleksandr Fotuima Precarpathian Vasyl Stefanyk National University, Ivano-Frankivsk, Ukraine Abstract The issue of the formation of value-motivational character of students of physical training and sports faculty by means of historical athletics heritage was actualized. The main periods of athletics development in Ivano-Frankivsk region were differentiated and presented. An integral indicator of development of students’ value-motivational character before and after the experimental curriculum implementation “History of athletics in Ivano-Frankivsk region” was studied. An integral professional developing component of the future specialists training curriculum in physical training and sports was determined. The positive development effect of experimental curriculum for the value-motivational character of students at institutions of physical training and sports was identified. Key words: values, motives, experimental curriculum, the history of athletics.